Exogenous Application of Calcium, α-Naphthaleneacetic Acid and 1Methylcyclopropene Improved Fruit Growth and Oil Yield of Oil Palm (Elaeis guineensis Jacq.) Grown on Ultisol - Sopandie, Didy; Hidayah, Agus Nur; Yahya, Sudirman (AGRIVITA Journal of Agricultural Science, 2024)
Soil acidity is one of the main factors limiting the growth and sustainable production of oil palm in Indonesia. The aim of this study was to evaluate the effect of various exogenous compounds on improving fruit growth and oil yield of palm oil grown on Ultisol. The experiment employed three treatments which were arranged in a Randomized Complete Block Design (RCBD) with three replications. The treatments were: 1-MCP (0, 100, 200, and 300 ppm), CaCl2 (0 and 50 ppm) and NAA (0 and 200 ppm). Application of Ca2+, NAA and 1-MCP either single or in combination improved fruit growth and oil yield by increasing almost all variables, except the number of bunches, bunch weight and fruit set. The 100 ppm 1-MCP + 50 ppm Ca2+ + 200 ppm NAA treatments showed the highest oil-to-dry mesocarp content. To get the highest oil to bunch (OB), the combination of 100 ppm 1-MCP + 200 ppm NAA; 50 ppm Ca2+ + 200 ppm NAA, and a single treatment of 50 ppm Ca2+ were very promising to be utilized.